No difference in follow-up estimated glomerular filtration rate between hypertensive and matched nonhypertensive kidney donors - Eun Hye Yang; Sung Shin; Young Hoon Kim; In Gab Jeong; Bumsik Hong; Chung Hee Baek; Hyosang Kim; Soon Bae Kim (Nefrología (English Edition), 2024)
Background: According to current guidelines, kidney donor candidates with controlled hypertension using 1 or 2 antihypertensive drugs may be considered as donor. However, this recommendation is based on the study that antihypertensive drug was initiated in mainly “after donor registration” and this may be white-coat hypertension because of donation-related anxiety. We compared the follow-up eGFR between kidney donors with preexisting hypertension and matched nonhypertensive donors. Methods: This single-center retrospective study classified 97 living hypertensive donors previously receiving antihypertensive drugs into two groups: 1 drug group (61 donors) and 2 drugs group (36 donors). We compared the follow-up eGFR between each donor previously receiving antihypertensive drugs and three matched nonhypertensive donors in terms of age, sex, and follow-up duration. Results: At a mean (range) of 51 months (12–214) in the 1 drug group, and 54 months (12–175) in the 2 drugs group after donation, there was no significant difference in follow-up eGFR between hypertensive donors previously receiving antihypertensive drugs and matched controls in each group and in total donors. There was no difference in the incidence of the patients with follow-up eGFR < 45 mL/min/m2 in each group and their matched controls. Multiple linear regression analysis showed that baseline eGFR was the only independent predictor for the final follow-up eGFR in the total donors. Conclusion: Our results support the current guidelines that donor candidates with controlled hypertension using 1 or 2 antihypertensive drugs may be considered as donors, and may increase the strength of this recommendation. Resumen: Antecedentes: Según las guías actuales, los candidatos a donantes con hipertensión controlada que utilicen 1 o 2 antihipertensivos pueden considerarse donantes. Sin embargo, esta recomendación se basa en el estudio en el que el fármaco antihipertensivo se inició principalmente «después del registro del donante» y esto puede ser hipertensión de bata blanca debido a la ansiedad relacionada con la donación. Comparamos la TFGe de seguimiento entre donantes de riñón con hipertensión preexistente y donantes no hipertensos compatibles. Métodos: Este estudio retrospectivo de un solo centro clasificó a 97 donantes hipertensos vivos que recibieron previamente fármacos antihipertensivos en dos grupos: 1 grupo de fármacos (61 donantes) y 2 grupos de fármacos (36 donantes). Comparamos la TFGe de seguimiento entre cada donante que recibió previamente fármacos antihipertensivos y tres donantes no hipertensivos compatibles en términos de edad, sexo y duración del seguimiento. Resultados: A una media (rango) de 51 meses (12-214) en el grupo de un fármaco y 54 meses (12-175) en el grupo de 2 fármacos después de la donación, No hubo diferencias significativas en la TFGe de seguimiento entre los donantes hipertensos que recibieron previamente fármacos antihipertensivos y los controles emparejados en cada grupo y en el total de donantes. No hubo diferencia en el número de pacientes con TFGe de seguimiento < 45 ml/min/m2 en cada grupo y sus controles emparejados. El análisis de regresión lineal múltiple mostró que la TFGe basal fue el único factor de riesgo independiente para la TFGe de seguimiento final en el total de donantes. Conclusión: Nuestros resultados apoyan las directrices actuales de que los candidatos a donantes con hipertensión controlada que utilizan 1 o 2 fármacos antihipertensivos pueden considerarse donantes y pueden aumentar la fuerza de esta recomendación.